2019
DOI: 10.1039/c9cc07266g
|View full text |Cite
|
Sign up to set email alerts
|

Cu(i)–SNS complexes for outer-sphere hydroboration and hydrosilylation of carbonyls

Abstract: Two new NHC–Cu(i)-[κ2-SNS] complexes were synthesized to directly compare the bifunctional catalytic activity of a hard amido vs. a soft thiolate donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The replacement of PNP pincer ligands with SNS ligands that contain more weakly σ-donating thioether groups in place of the phosphine donors may be a useful approach to lowering the electron density at the metal. In fact, SNS pincer ligands have already been used to support base metal , and palladium , catalysts due to their relative air stability, facile synthesis, and potential hemilability compared to the PNP ligand platform. For example, palladium catalysts with either pyridyl or aliphatic SNS ligands can facilitate cross-coupling reactions that are proposed to involve homogeneous or heterogeneous active species.…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of PNP pincer ligands with SNS ligands that contain more weakly σ-donating thioether groups in place of the phosphine donors may be a useful approach to lowering the electron density at the metal. In fact, SNS pincer ligands have already been used to support base metal , and palladium , catalysts due to their relative air stability, facile synthesis, and potential hemilability compared to the PNP ligand platform. For example, palladium catalysts with either pyridyl or aliphatic SNS ligands can facilitate cross-coupling reactions that are proposed to involve homogeneous or heterogeneous active species.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are only two examples on the hydroboration of ketones catalyzed by molecular zinc hydrides (Figure D,E). , It should be noted that no zinc catalysts are available in literature, which performs for both hydrosilylation and hydroboration of many ketones (bifunctional), except D and E, which are limited to only one substrate. However, very recently, the Baker group reported a copper-based catalyst for hydroboration and hydrosilylation of carbonyls …”
Section: Introductionmentioning
confidence: 99%
“…14 In contrast, copper complexes with an N-heterocyclic carbene ancillary ligand showed κ 2 -SNS Me binding with the thiolate complex also serving as an efficient (0.5 mol %, RT) outer-sphere carbonyl hydroboration catalyst (Scheme 1C). 16 In another finding relevant to this work, we showed that electron-rich ancillary ligands led to selective C aryl −S bond cleavage with subsequent formation of a coordinated dianionic CNS pincer ligand (Scheme 2). 15,20 For nickel, there are three relevant previous reports.…”
Section: ■ Introductionmentioning
confidence: 68%
“…Transition metal complexes bearing “pincer” ligands tend to exhibit improved thermal stability, reactivity, and catalytic activity/selectivity when compared to their monodentate analogs. Inspired by a plethora of multiple N,S coordination geometries in metallo-enzymes and their synthetic models, , we have been preparing new first row metal SNS complexes (Figure ) in order to assess and compare the roles of “hard” amido and “soft” thiolate donors as cooperative ligands in catalysis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation